IMPACT ON PROFIT, CASH FLOW, COMPANY SIZE AND FINANCIAL DISTRESS - Zuhrianto, Liza; Mulyani, Sri; Wijayanti Daniar Paramita, Ratna (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
The purpose of this study was to determine the effect of earnings, cash flow, and firm size on the financial distress of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2018. This type of research is quantitative research. The type of data in this study is secondary data. Data analysis techniques used multiple linear regression analysis. This study uses a purposive sampling technique to get samples according to specified criteria. The number of samples selected based on the criteria in this study is 32 companies with a population of 38 manufacturing companies in the consumer goods industry sector, which are listed on the Indonesia Stock Exchange in 2016-2018. The results showed that profits measured using a return on assets affect financial distress